Dysregulated Microbiota-Driven Gasdermin D Activation Promotes Colitis Development by Mediating IL-18 Release - Gao, Hanchao; Cao, Mengtao; Yao, Yikun; Hu, Wenjun; Sun, Huimin; Zhang, Yingwei; Zeng, Changchun; Tang, Jia; Luan, Shaodong; Chen, Pengfei (Frontiers in Immunology, 2021)
The balance between gut microbiota and host is critical for maintaining host health. Although dysregulation of the gut microbiota triggers the development of various inflammatory diseases, including colitis, the molecular mechanism of microbiota-driven colitis development is largely unknown. Here, we found that gasdermin D (GSDMD) was activated during acute colitis. In the dextran sulfate sodium (DSS)-induced colitis model, compared to wild-type mice, Gsdmd-deficient mice had less colitis severity. Mechanistically, GSDMD expression in intestinal epithelial cells (IECs), but not infiltrating immune cells, was critical for GSDMD-mediated colitis progression. Moreover, commensal Escherichia coli (E. coli) largely overgrew during colitis, and then the dysregulated commensal E. coli mediated GSDMD activation. Furthermore, the activated GSDMD promoted the release of interleukin-18 (IL-18), but not the transcript or maturation level of IL-18, which in turn mediated goblet cell loss to induce colitis development. Thus, GSDMD promotes colitis development by mediating IL-18 release, and the microbiota can mediate colitis pathogenesis through regulation of GSDMD activation. Our results provide a potential molecular mechanism by which the microbiota-driven GSDMD activation contributes to colitis pathogenesis.